2019
DOI: 10.1186/s12893-019-0476-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessement of postoperative long-term survival quality and complications associated with radical antegrade modular pancreatosplenectomy and distal pancreatectomy: a meta-analysis and systematic review

Abstract: BackgroundThis study evaluated the perioperative complications and the long-term pancreatic survival outcomes in patients treated with radical antegrade modular pancreatosplenectomy (RAMPS) and distal pancreatectomy (DP).MethodWe performed a computer search on the PubMed, Embase and Cochrane Library databases to retrieve the RCT or clinical trials comparing RAMPS and DP published before July of 2018. The quality of the included trials was assessed according to the inclusion and exclusion criteria by two resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
1
31
1
Order By: Relevance
“…The procedure was named "RAMPS," and at present, it is performed extensively worldwide as the primary procedure for advanced cancer of the pancreatic body and tail. [23][24][25][26] RAMPS and our proposed DP-TCR procedure aim to achieve histologically radical surgery. Both procedures have the same philosophy in that they attempt to resect the retroperitoneum en bloc with the pancreatic body and tail and the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was named "RAMPS," and at present, it is performed extensively worldwide as the primary procedure for advanced cancer of the pancreatic body and tail. [23][24][25][26] RAMPS and our proposed DP-TCR procedure aim to achieve histologically radical surgery. Both procedures have the same philosophy in that they attempt to resect the retroperitoneum en bloc with the pancreatic body and tail and the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported a few years ago that, compared with SRPS, RAMPS showed significant improvement in R0 resection rate and 5-year survival rate [5,6] . However, reports in recent years have shown that despite the theoretic advantages of RAMPS over SRPS, high-level evidence that demonstrates a survival benefit with RAMPS does not currently exist [7,8]. RAMPS 'potential survival advantage still needs to be proven.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Indeed, a recent meta-analysis demonstrated that minimally invasive DPS had comparable 5-year survival to open surgery with significantly lower positive margin rates, shorter in-patient hospital stay, less blood loss, and lower patient morbidity and mortality [64]. As discussed above, the data on RAMPS is limited by analysis of retrospective data which demonstrate that there is no increase in POPF, complications, and mortality but a significantly improved R0 rate and number of lymph nodes resected [65]. Although as Cao et al state further, trial data are needed before confirmation of the survival benefits of RAMPS which can be assessed although the authors state that based upon their meta-analysis, RAMPS is an oncologically superior procedure [66].…”
Section: Distal Pancreatectomy and Splenectomy (Dps)mentioning
confidence: 99%